PHOTO-LUMINESCENCE STUDIES OF DEEP TRAPS IN GAP-NI - Hayes, W; Ryan, J; West, C; Dean, P (1979)
Transition metal impurities act as deep trapping centres in III-V and II-VI compounds and give rise to near-infrared absorption and luminescence. In many cases the charge state of the ion participating in these optical transitions is either unknown or the subject of some controversy. Luminescence studies of GaP:Ni are described. Measurements of polarised spectra under application of uniaxial stress support the assignment of the charge state Ni+ (d9).